THE ROLE OF SIMULATION TRAINING IN THE FORMATION OF PROFESSIONAL COMPETENCE OF STUDENTS OF MEDICAL HIGHER EDUCATION INSTITUTIONS (Academicia Globe: Inderscience Research, 2021)
Simulation training is a mandatory component in professional training, which provides each student with the opportunity to perform professional activities in accordance with professional standards and rules for the provision of medical care.In order to determine the effectiveness of the use of training simulators in the process of preparing students of a medical institute for practice, a study was carried out in two groups. Reliable results were obtained in students enrolled in the Clinical Skills Training Laboratory (simulation center) who performed practical skills more than three times on simulators - artificial respiration, airway patency restoration, pulse counting, auscultation of the heart, blood pressure measurement, closed heart massage up to 65 , 7%, as well as gastric sounding, setting a cleansing enema, bladder catheterization, digital rectal examination - 52.5%, and self-confidence in performing cardiopulmonary resuscitation was assessed - 38.2%.The use of phantoms, dummies and dummies in the educational process has a greater effect than just a lecture format of training and does not pose a risk to human life.